2020
DOI: 10.1177/0003319720939466
|View full text |Cite
|
Sign up to set email alerts
|

Computed Histological Quantification of Atherosclerotic Plaque Microcalcifications

Abstract: Inflammation has a central role in atherosclerotic plaque formation and rupture. Intense macrophage inflammatory activity results in microcalcifications which are strongly associated with plaque vulnerability. Microcalcifications with specific critical size between 5 and 65 μ, located in the fibrous cap producing local mechanical stress on the plaque surface and may directly contribute to plaque rupture. Hence, accurate assessment of microcalcifications size and dimension has significant clinical impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The commonest presentation of coronary atherosclerosis is plaque formation at the site of bifurcation, although not always exclusively, as plaques may also develop at mid-arterial segments. These atherosclerotic coronary manifestations are identified based on conventional angiographic examination [ 44 , 45 ]. Additional atherosclerosis manifestations in the segments that look normal on angiography can be detected by the presence of atherosclerotic plaques on CT examination [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The commonest presentation of coronary atherosclerosis is plaque formation at the site of bifurcation, although not always exclusively, as plaques may also develop at mid-arterial segments. These atherosclerotic coronary manifestations are identified based on conventional angiographic examination [ 44 , 45 ]. Additional atherosclerosis manifestations in the segments that look normal on angiography can be detected by the presence of atherosclerotic plaques on CT examination [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal imaging studies, using PET, have shown that inflamed arterial sites undergo the subsequent deposition of calcium, and within the same arterial segment, different degrees of inflammation show different rates of calcium deposition [ 106 ]. The death of macrophages and smooth muscle cells release vesicles acting as nucleating sites for the deposition of hydroxyapatite crystals which can aggregate, resulting in microcalcifications less than 50 µm in diameter being embedded in the fibrous cap [ 107 , 108 ]. Plaque calcification further stimulates macrophage infiltration, thus increasing the nucleating sites and new calcification [ 109 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, inflammation has a key role in atherosclerotic plaque formation and rupture. Intense macrophage inflammatory activity results in microcalcifications which are strongly associated with plaque vulnerability (27). The pioneering work of Vengrenyuk (28) attributed cap rupture to microcalcification within the cap (29).…”
Section: Calcification and Plaque Vulnerabilitymentioning
confidence: 99%